Evaluation of the Efficacy of Ultrasound-Guided Interventions in Managing First-Trimester Vaginal Bleeding - Aasma Naz, Hafiza Khatoon, Abid Hussain Jamali, Fozia Irum, Kiran Memon, Shazia Ahmed Jatoi, Kiran Aamir, Aamir Ramzan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Aim was to evaluate the efficacy of ultrasound-guided interventions in managing first-trimester vaginal bleeding. Study Design: Observational study Place and Duration: Gynaecology and Obstetrics Department people university of Medical and health sciences jamshoro Hyderabad. January 2022-December 2022 Methods: Total 116 pregnant females of first trimester were presented in this study. All the presented women had complaint of vaginal bleeding. Included patients had gestational age between 6-12 weeks. After a thorough clinical evaluation and diagnosis, patients were sent for an ultrasound. Ultrasound results were evaluated in terms of pregnancy type and types of abortions. SPSS 23.0 was used to analyze all data. Results: There were majority primi-gravida women 72 (62.1%) and 44 (37.9%) females were multigravida. Females mean age 27.5±12.19 years and had mean BMI 27.8±4.23 kg/m2. Mean gestational age of the females was 10.2±4.17 weeks. Frequency of viable patients was 36 (31.03%) and non-viable patients was 80 (68.97%). Among 80 non-viable cases, different type of abortions was found in 62 (67.5%) cases, ectopic pregnancy in 10 (12.5%) cases and molar pregnancy in 8 (10%) cases. Conclusion: Ultrasonography is the most accurate and non-invasive diagnostic method for distinguishing between the various conditions and phases of first trimester bleeding in pregnant women. The use of ultrasonography for prenatal screening has opened up new avenues for the timely treatment of patients, which has been shown to minimize death rates associated with pregnancy complications. Keywords: Abortion, First Trimester, Molar pregnancy, Ectopic Pregnancy